Book review: Researching, teaching and the practice of mathematical modelling and applications - Stillman, Gloria (NOMAD Nordic Studies in Mathematics Education, 2007)
Christopher Haines, Peter Galbraith, Werner Blum, and Sanowar Khan (Eds.) (2007), Modelling ICTMA12: Education, Engineering and Economics. Chichester, UK: Horwood Publishing. ISBN-13: 978-1-904275-20-6